2022
DOI: 10.1002/jcsm.12976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D monotherapy on indices of sarcopenia in community‐dwelling older adults: a systematic review and meta‐analysis

Abstract: Background Vitamin D supplementation is proposed as a potentially effective nutritional intervention to mitigate the risk of sarcopenia. The aim of this systematic review and meta-analysis was to investigate the impact of vitamin D supplementation monotherapy on indices of sarcopenia in community-dwelling older adults. Methods A comprehensive search of the literature was conducted in PubMed, Web of Science, Scopus, and Cochrane Library. Eligible randomized controlled trials (RCTs) compared the effect of vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…Pfeifer et al reported that vitamin D could improve muscle mass in the elderly (53), but some researchers reported no significant improvement in muscle mass or strength by vitamin D (54,55). Moreover, a meta-analysis of the effect of vitamin D monotherapy on sarcopenia showed that vitamin D supplementation had no effect on muscle mass (appendicular lean mass) and muscle strength (handgrip strength) and muscle performance parameters except SPPB (56). The leucinecombined supplementation including vitamin D might be more effective than leucine-or vitamin D-isolated supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Pfeifer et al reported that vitamin D could improve muscle mass in the elderly (53), but some researchers reported no significant improvement in muscle mass or strength by vitamin D (54,55). Moreover, a meta-analysis of the effect of vitamin D monotherapy on sarcopenia showed that vitamin D supplementation had no effect on muscle mass (appendicular lean mass) and muscle strength (handgrip strength) and muscle performance parameters except SPPB (56). The leucinecombined supplementation including vitamin D might be more effective than leucine-or vitamin D-isolated supplements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in the past that a number of dietary supplements may prevent or lessen severe symptoms. A diet rich in protein benefits health, aids in the recovery of sick people, and maintains functional status in elderly people (Prokopidis et al, 2022a). An efficient method for improving muscle growth and strength as well as overall physical performance in older persons is the combination of resistance training and post-exercise protein supplementation (Khor et al, 2022;Velasco et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…9 There are systematic review and meta-analysis of randomized controlled trials raised that vitamin D supplementation has a small positive impact on muscle strength, 10 even vitamin D supplementation did not improve any sarcopenia indices in community-dwelling older adults and may compromise some aspects of physical performance. 11 However, a lack of clinically compelling evidence linking to muscle mass and even muscle metabolism and a lack of consensus on the pathological serum level and supplements of vitamin D on the muscle aspects still exist.…”
Section: Introductionmentioning
confidence: 99%